Atherosclerotic plaque metabolism in high cardiovascular risk subjects – A subclinical atherosclerosis imaging study with 18F-NaF PET-CT. (May 2017) - Oliveira-Santos, Manuel de; Castelo-Branco, Miguel; Silva, Rodolfo; Gomes, Andreia; Chichorro, Nuno; Abrunhosa, Antero; Donato, Paulo; Pedroso de Lima, João; Pego, Mariano; Gonçalves, Lino; Ferreira, Maria João
Abstract: Background and aims: Atherosclerotic plaque molecular imaging with 18 F-sodium fluoride (NaF) in positron emission tomography with computed tomography (PET-CT) provides potential discrimination between active unstable microcalcification and established dormant calcification. We aimed to study 18 F-NaF atherosclerotic plaque uptake in high cardiovascular (CV) risk participants and its associations with CV risk factors, coronary calcium score and thoracic fat volume. Methods: High CV risk hypertensive individuals from a single centre were prospectively scanned with 18 F-NaF-PET-CT in the coronary, aortic and carotideal arteries. Atherosclerotic plaque 18 F-NaF uptake was expressed as Corrected Uptake per Lesion (CUL): maximum standard uptake value in each vascular territory subtracted by mean blood pool activity. Results: Mean age was 64 years, 56% male and 96% Caucasian (n = 25). Ninety six per cent of the subjects showed 18 F-NaF uptake in the aorta (CUL 0.9 ± 0.3), 40% in the carotid arteries (median CUL 0.0, IQR 0.0–0.7) and 64% in the coronary arteries (0.4, IQR 0.0–0.6). Individuals with ≥ five risk factors (60%) had increased overall 18 F-NaF uptake (1.1 ± 0.3 vs . 0.7 ± 0.3, p  < 0.01), which was positively correlated with predicted fatal CV risk - SCORE (r = 0.49, p  = 0.01). There was no correlation between 18 F-NaF uptake in the coronary arteries and calcium score ( p  = 0.87). Thoracic fat was moderately correlated with overall CUL (r = 0.41, p  = 0.04). Conclusions: In a high CV risk group, 18 F-NaF atherosclerotic plaque uptake was related to the burden of CV risk factors and thoracic fat volume, but there was no association between coronary uptake and calcium score. Highlights: Study of 18 F-NaF atherosclerotic plaque uptake in high cardiovascular (CV) risk individuals – micro-calcification marker. Proportion of uptake: 96% in the aorta, 40% in the carotid and 64% in the coronary arteries. 18 F-NaF plaque uptake is related to the burden of CV risk factors, predicted fatal CV risk and thoracic fat volume. No correlation between 18 F-NaF uptake in the coronary arteries and calcium score.